Therapeutic effects and mechanisms study of Hanchuan Zupa Granule in a Guinea pig model of cough variant asthma. (6th April 2021) - Li, Pengfei; Wang, Jingkang; Wang, Chunguo; Cheng, Long; Ma, Quantao; Li, Yaqi; An, Yongcheng; Dai, Hongyu; Duan, Yuhui; Wang, Tieshan; Ma, Xuan; Zhang, Minghui; et al.
Abstract: Ethnopharmacological relevance: Hanchuan Zupa Granule (HCZP), a traditional Chinese ethnodrug, has the functions of supressing a cough, resolving phlegm, warming the lungs, and relieving asthma. In clinical practice employing traditional Chinese medicine (TCM), HCZP is commonly used to treat acute colds, cough and abnormal mucous asthma caused by a cold, or "Nai-Zi-Lai" in the Uygur language. Studies have confirmed the use of HCZP to treat cough variant asthma (CVA) and other respiratory diseases. However, the pharmacological mechanisms of HCZP remain unrevealed. Aim of the study: To investigate the anti-tussive and anti-asthmatic effects and the possible pharmacological mechanisms of HCZP in the treatment of CVA. Materials and methods: A guinea pig CVA animal model was established by intraperitoneal injection of ovalbumin (OVA) combined with intraperitoneal injection of aluminium hydroxide adjuvant and atomized OVA. Meanwhile, guinea pigs with CVA received oral HCZP (at dosages of 0.571, 0.285 and 0.143 g/kg bodyweight). The number of coughs induced by aerosol capsaicin was recorded, and the airway hyperresponsiveness (AHR) of CVA guinea pigs was detected with the FinePointe series RC system. H&E staining of lung tissues was performed to observe pathological changes. ELISA was used to detect inflammatory cytokines. qRT-PCR and western blotting analyses were used to detect the expression of Th1-specific transcription factor (T-bet), Th2-specific transcription factor (GATA3), and Toll-like receptor 4 (TLR4) signal transduction elements. These methods were performed to assess the protective effects and the potential mechanisms of HCZP on CVA. Results: Great changes were found in the CVA guinea pig model after HCZP treatment. The number of coughs induced by capsaicin in guinea pigs decreased, the body weights of guinea pigs increased, and inflammation of the eosinophilic airway and AHR were reduced simultaneously. These results indicate that HCZP has a significant protective effect on CVA. A pharmacological study of HCZP showed that the levels of interleukin-4 (IL-4) and IL-5 and tumour necrosis factor-α (TNF-α) in serum decreased. The amount of interferon-γ (IFN-γ) increased, mRNA and protein expression of TLR4 and GATA3 weakened, and mRNA and protein expression of T-bet increased. Conclusions: HCZP ameliorated the symptoms of guinea pigs with CVA induced by OVA by regulating the Th1/Th2 imbalance and TLR4 receptors. Graphical abstract: Image 1